Peran Teknologi dalam Pengelolaan Sumber Daya Ekonomi Kreatif pada Industri Kreatif di Kecamatan Medan Marelan - Erni Susilawati Purba; Kristin Margaretha Simarmata; Sernanda putri Darma; Putri Kemala Dewi Lubis (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to determine the role of technology in managing creative economic resources in the creative industry in Medan Marelan District. This research was conducted using qualitative methods through interviews with one of the MSME owners in Medan Marelan District. The research results show that technology has an important role in managing creative economic resources in the creative industry, namely increasing efficiency and productivity, increasing global market access, and improving market information and marketing strategies. This research also shows that managing creative economic resources requires a significant role of technology. Technology not only functions as a tool, but also as a driver and developer. Thus, management of creative economy resources must consider how technology can be used to increase efficiency and productivity in the creative industry.